Relationship between the order of immune-biological administration and pain management in children during vaccination procedure - Dilana López Borbón (Universidad de Costa Rica, 2013)
The aim of this research had been in evidence if the administrative order of the immune-biological has implications in the pain response from an infant during vaccination. The pain could promote a negative perspective related to the immunization, especially in children and their parents. For that reason, an adequate pain management during vaccination could have as a consequence a better acceptance of the immunization program by the society. During the research, the methodology that had been applied was based evidence clinical practice. Firstly, It had been necessary formulated a PICO question. Secondly, the best articles had been found after searching in databases as PubMed, Medline, Cochrane and Tripdata base. These five articles had been evaluated through the critical analysis using CASPe template. As a result, the order in the administration of immune-biological has consequences in the pain response of the child. To conclude, it is important to note that the order of immune-biological and child pain response have relating. So, it is necessary to administrate the painful vaccine at the end in order to have a better management of childhood pain. Additionally, it is important to do more researches about the specific order that vaccines would be administrated.